Feedmypet: alimentador automático de animais de estimação - Dallastela, Emílio Gabriel (2021)
During the 2020 pandemic, the Brazilian population had to stay at home for more than a year, which caused a growth in the incorporation of pets in Brazilian homes. As countries are increasingly opening their borders for travel, there was a need to take care of pets remotely. To solve this problem, the project proposal was to develop an automatic pet feeder, with water and food reservoirs, remotely controlled by a native mobile application. Through this mobile application, the user registers an account and configures the times and portions of their pets meals. The development of this project was divided into different parts, mechanics, hardware, firmware, and software. Initially, in the mechanical part, a model for 3D printing was designed, but the 100% increase in the price of the material made its production unfeasible. As a solution, the same model was created in MDF (Medium Density Fiberboard), a type of wood. In the hardware, a PCB was designed and printed to connect different components and modules. The following parts were soldered on this board: an ADC module responsible for reading two 5kg load cells, a DRV8825 driver responsible for controlling a stepper motor, components responsible for activating a water pump, and a Raspberry Pi Zero W, as well as connectors for powering the circuit. For the creation of the mobile application, the React Native framework was chosen, which makes it possible to develop native applications for both Android and iOS. During development, the Expo tool was used to simulate and later export the application for use. On the server side, the Node.js Express framework was used for development, and the Heroku service was used for hosting it. A non-relational database, called MongoDB, was created and hosted on the MongoDB Atlas service. To control the actuators and read the sensors on the Raspberry Pi Zero W, a Python script was developed, which was scheduled to run every minute on its operating system, Linux. In the final tests the product worked as expected during two days in a row, therefore it was a success in terms of functionality. Taking into account the costs in the prototype production and its unique benefits in comparison to the other products in the market, its price would be competitive. The project was also a success from the learning point of view for incorporating different areas and current technologies in a single project.